The New Zealand Police Early Intervention System: A review of implementation and impact issues - Briody, Michael (International journal of police science & management, 2020)
This paper examines the implementation process and impacts of an Early Intervention System (EIS) introduced into the New Zealand Police in 2013. The system was associated with large reductions in complaints of 72.5% against target employees (N = 526), but without this clearly translating into reductions in the overall number of complaints. The New Zealand case also highlighted the issue of the different potential uses of early intervention. Should the priority be officer welfare or the more usual aim of improving officer conduct, police-citizen relations and public confidence in police? The authors argue that the traditional focus on reducing adverse incidents between police and citizens, with public complaints as a major guide and measure, should have at least equal weight in an EIS that is part of a comprehensive state-of-the-art police integrity management system. The paper also highlights the need for detailed publicly accessible data to ensure accountability of investments in integrity strategies.